Daridra Perspektif Susastra Hindu - I Putu Agus Aryatnaya Giri; Kadek Dwi Sentana Putra; Kadek Agus Yoga Dwipranata; I Ketut Wiratmaja (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
Poverty in general often reveals a negative side that haunts life, especially the life of someone who is not culturally educated to think revolutionary, especially related to a better life welfare. From the perspective of Hindu religious literature, of course poverty is very interesting to review, especially in breaking through the cultural paradigm of thinking that wallows in "decline". The method used in this research is a qualitative research method. Data collection techniques in this study used library research. The results of the study show that the Sarasamuscaya book, as one of the Hindu literature, discusses that it is really unpleasant to be poor, especially poor people who are stupid, as the saying goes "has fallen down a ladder", because if we are stupid and poor, whatever we say will not be paid any attention to person. Therefore, one way to be free from the shackles of poverty is to work (karma). Of course, we use the property obtained to meet the necessities of life which must be sought on the basis of dharma so that our lives do not fall into the valley of suffering. Poverty is not only oriented to the problem of material possessions, but also to the aspect of morality, because many people who are rich in wealth but poor in morality are like "officials" who commit acts of corruption, as well as people who are physically healthy and of productive age who choose to become beggars. seem lazy to work. To minimize this, of course the government must actively socialize about character education and make it happen by providing free formal education to people who are economically disadvantaged. So that education can be accessed by everyone regardless of social status.